Efectos de la miel de abeja en la carbonatación natural de una cerveza artesanal elaborada a partir de cebada (Hordeum vulgare) y quinoa (Chenoponium quinoa) - Moscoso Buitrón, Esteban Francisco (2019)
The main objective of the study was to evaluate the effects of honey on the natural carbonation in a beer made from barley and quinoa. The formulation of the beer was 75 percent of barley malt and 25 percent of quinoa malt. The quinoa species that worked is Tunkahuan, that species was developed by INIAP, the principal characteristics was low level of saponin. The purpose of malting process was to increase the amount of fermentable sugars. The beer developed was a high fermentation that passed in fermentation tank about 21 days and then for the second fermentation included 3 variables: honey, sugar and a mixture of sugar and honey, another variable that was used were days of second fermentation (4 and 8 days). For analyzes the samples propose 4 physical-chemical analyzes: alcohol content, carbonation, acidity and pH. Subsequently, for statistical analyzes (ANOVA) were performed to investigate if there are significant differences. Later the other step was made sensory analysis with 30 consumers, the consumers test the 6 samples and they qualify them preference. The physical-chemical results of 6 samples, had a good performance because the parameters that demand the norm INEN 2262, demonstrate that all treatments participate in the production of alcohol and CO2. In the sensorial analyze the consumers rated as the most accepted, the sample with honey and 4 days of second fermentation, this condition verified that the honey helps in the process of natural carbonation and makes a difference in the preference of consumers.